Bee-Proofing for Florida Citizens - Michael K. O’Malley; James D. Ellis; Anita S. Neal (EDIS)
ENY-143, a 5-page illustrated fact sheet by M. K. O’Malley, J. D. Ellis, and A. S. Neal, provides information about Africanized honey bees (AHB), precautions that can be taken by Florida residents to locate potential nesting sites, prevent nests from forming, and how to inspect one's property for nests. Published by the UF Department of Entomology and Nematology, December 2007.